A STUDY ON RISK FACTORS OF ASTHMA IN RURAL POPULATION OF COASTAL ANDHRA PRADESH, INDIA - A. KANAKA RAJU; K. SUNITHA; P. V. V. SATISH; K. SUNITA; G. SUDHAKAR (International Journal of Pharma and Bio Sciences, 2013)
The objective of the present communication was to study the prevalence and risk factors of asthma patients from rural areas of coastal districts i.e., Guntur, West Godavari and Visakhapatnam of Andhra Pradesh. Two twenty nine (229) asthma patients were selected for the study from November 2010 to April 2012. A questionnaire was designed for collecting the information of asthma cases regarding socio-demographic data, Body Mass Index (BMI), environmental risk factors that develop asthma. From out of 229 subjects, 92(40.17%) were males and 137(59.83%) were females. Regarding the risk factors of asthma; 96.51% was effected by weather change, 67.69% by pollengrains, 60.66% by cooking fumes and 37.48% by allergy. Regarding smoking and alcoholism; 13.54% of the subjects were smokers, 17.91% of the subjects were alcoholics and 69.55% of the subjects were non-smokers. Thus the present investigation shows that asthma is an important public health problem in rural areas. It also revealed that occupation, smoking, hereditary are the other causes for increasing the incidence of asthma.